Prevalence of teen dating violence and the associations with substance use and externalizing behaviors in Nicaraguan early adolescents. Issue 2 (17th June 2020) - Lu, Yu; Shin, Youngju; Le, Vi D.; Temple, Jeff R.; Pettigrew, Jonathan
Abstract : Purpose: Despite being a significant public health problem, teen dating violence and related risk behaviors are yet to be examined in Nicaragua. This study aims to examine the prevalence of in-person dating violence and cyber dating abuse and to test the associations between teen dating violence and substance use (i.e. alcohol, cigarette, marijuana and e-cigarette) as well as externalizing behaviors. Design/methodology/approach: Survey responses were collected from a school-based sample of 1, 799 Nicaraguan early adolescents (average age = 13.04 years). Findings: The prevalence was 41% for in-person dating violence victimization, 39% for in-person dating violence perpetration, 30% for cyber dating abuse victimization and 26% for cyber dating abuse perpetration. The majority (56%) of the adolescents reported engagement in externalizing behaviors, but substance use prevalence was relatively low, ranging from 1–9% depending on the substance type. Multivariate regression analyses suggest that in-person dating violence perpetration was positively associated with all types of substance use and externalizing behaviors, while victimization was only associated with externalizing behaviors. Originality/value: Despite the descriptive nature, the study is the first to examine the prevalence of teen dating violence and its relationships with other risk behaviors in Nicaraguan adolescents and have important health implications.